Effects of feeding juniper as a roughage on feedlot performance, carcass measurements, meat sensory attributes, and volatile aroma compounds of yearling Rambouillet wethers1, 2. (17th May 2019) - Kerth, Christopher R; Wall, Kayley R; Miller, Rhonda K; Whitney, Travis R; Stewart, Whitney C; Boles, Jane A; Murphy, Thomas W
Abstract: The majority of U.S. lambs are born during late winter or early spring, which can create downstream variability in carcass quality if commercial lamb harvest is to be relatively constant throughout the year. Flavor is an important quality determining characteristic of sheep meat and is influenced, in part, by animal age at harvest. However, management practices to mitigate the risk of objectionable flavors in meat from old crop lambs or yearlings are not well known. Yearling (16.8 ± 0.14 mo) Rambouillet wethers were assigned to 1 of 3 treatment groups, which consisted of feeding a 20% ground sorghum-sudangrass hay diet for 40 d (JUN0; n = 10), a 20% ground juniper diet for 40 d (JUN40; n = 10), or a 20% ground hay diet for 20 d followed by a 20% ground juniper diet for 20 d (JUN20; n = 10). Wethers were harvested on day 41 and a whole bone-in loin and a boneless inside leg roast were fabricated from one side each of carcass. After grilling (loin chop) or convection air roasting (leg roast), trained sensory panel evaluation and measurement of aroma volatiles by gas chromatography/mass spectrometry were performed. Treatment diet did not affect ( P ≥ 0.17) wether feedlot performance, dressing percentage, or loin eye area. However, wethers fed JUN0 tended ( P = 0.06) to have greater back fat depth than wethers fed JUN20 or JUN40. No trained sensory panel trait of loin chop samples was affected ( P > 0.10) by treatment. Leg roasts from JUN0 and JUN20 wethers had greater ( P = 0.01) lamb identification sensory score than JUN40. Benzaldehyde, 1-heptanol, and 1-octanol concentrations were greater ( P < 0.05) and decanal and nonenal concentrations were less ( P < 0.05) in loin chops from JUN0 compared with JUN40 wethers. Additionally, the terpenes cedr-8-ene, gamma muurolene, and widdrene tended to be greater ( P < 0.07) in loin chops from JUN20 and JUN40 than JUN0 wethers. The 2-pentyl-furan concentrations were greatest ( P = 0.03) in leg roasts from JUN40 wethers. Like the loin chops, cedr-8-ene, gamma-muurolene, toluene, and widdrene were greater ( P < 0.05) in leg roasts from wethers fed either of the juniper diets compared with JUN0. Yearling wethers can be finished on a feedlot diet containing 20% juniper for up to 40 d prior to harvest with no impact on feedlot performance, carcass characteristics, nor negative impact on sensory attributes or volatile compounds of either grilled loin chops or roasted legs.